Slavery and unfree labour in Nepal: documents from the 18th to early 20th century - Cubelic, Simon; Khatiwoda, Rajan; Michaels, Axel (Documenta Nepalica, 2022)
The topic of slavery is largely under-represented in the historiography of Nepal. This source book, aware of this disparity and wishing to encourage future studies on the topic, provides the reader with editions, translations and a study of selected documents and legal texts of Nepal from the period of the eighteenth to the early twentieth century. These sources are concerned with such different aspects of slavery as donations, transactions, bondservitude, forced labour, emancipation, and law
Keywords: 18. Jahrhundert (1700 bis 1799 n. Chr.); 19. Jahrhundert (1800 bis 1899 n. Chr.); Erste Hälfte 20. Jahrhundert (1900 bis 1950 n. Chr.); Nepal; Konferenzschrift -- 2019 -- Patan; Quelle; Geschichte 1700-1950; Recht; Zwangsarbeit; Sklaverei